2018
DOI: 10.3846/tede.2018.5212
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Poverty Cycles in the U.S. 1959–2013

Abstract: This paper aims to shed light on the nature of poverty as a dynamic process by examining poverty cycles, their magnitudes, and their asymmetry. The designated benchmark country is the USA due to the availability of time series data making comprehensive analyses possible. We use Harding and Pagan (2002) and the Cardinale and Taylor (2009) model to isolate poverty cycles in the U.S. during 1959–2013. Once isolated, we test the poverty cycles for duration dependency, and their synchronization with the U.S. busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Driven by business cycles, the emergence of poverty is also apparently cyclical. This was confirmed in a study by Skare et al (2018). Once poverty cycles occur, it tends to have an impact on many aspects of social development, like economic crises, insufficient public services and social exclusion (Bourguignon & Chakravarty, 2003;Zhou & Liu, 2019) .…”
Section: Background and Related Literaturementioning
confidence: 65%
See 3 more Smart Citations
“…Driven by business cycles, the emergence of poverty is also apparently cyclical. This was confirmed in a study by Skare et al (2018). Once poverty cycles occur, it tends to have an impact on many aspects of social development, like economic crises, insufficient public services and social exclusion (Bourguignon & Chakravarty, 2003;Zhou & Liu, 2019) .…”
Section: Background and Related Literaturementioning
confidence: 65%
“…Therefore, an appealing argument is put forward in this paper: poverty cycle theory evolved from business cycle theory, and just as business cycle theory evolved from crisis theory (Schiaffino et al, 2017). Skare et al (2018) also reported this finding, business cycles and poverty cycles are two faces of the same coin. Since then, the research on 'income' has remained high and always been in the top three ranks.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Many experts and scholars have attempted to explore the causes of poverty from different views using different methods (Carneiro et al, 2016;Wang & Qian, 2017;Aristondo, 2018;Skare et al, 2018;Boemi & Papadopoulos, 2019). These existing studies have been mostly based on traditional single-level linear or spatial statistical regression models, such as orthogonal least squares (OLS) regression, least squares regression, multiple linear regression, and spatial regression models (Behruz et al, 2014;Guo et al, 2018;Peirovedin et al, 2016;Thongdar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%